Estimating the Inbreeding Rate in Natural Populations of The Black-Naped Fruit Dove (Ptilinopus melanasphila) - Sariffudin Fatmona; Sri Utami; Jailan Sahil (Jurnal Penelitian Pendidikan IPA, 2024)
This research aimed to determine the population of the Black-Naped Fruit Dove (Ptilinopus melanasphila) by estimating population size, sex ratio, effective population, and inbreeding rate, providing a basis for ex-situ design considerations. Data collection employed survey techniques such as the line transect and concentration count point methods. Data analysis focused on determining population size, sex ratio, effective population, and inbreeding rate. The research was conducted in the Sula Islands, North Maluku. Observations and discussions were conducted separately for each location to obtain empirical and comprehensive data serving as a reference for further research. Results revealed the inbreeding rates at the research locations were observed as follows: Soamole village (1.42%), Wai Ipa village (1.56%), and Bega village (1.60%). Sex ratios were observed as follows: Soamole village (male : female ratio of 22.17 : 85.38), Wai Ipa village (male : female ratio of 19.48 : 73.78), and Bega village (male : female ratio of 19.61:80.39). Effective populations were observed as follows: Soamole village (22.39 heads), Wai Ipa village (16.48 heads), and Bega village (16.08 heads). The inbreeding rate is in the good category, while the population number, sex ratio and effective population are in the medium category, however habitat destruction and continuous excessive hunting can result in decline and extinction.